ZINGIBER OFFICINALE L – BOTANICAL DESCRIPTION OF THE PLANT (World Bulletin of Public Health, 2024)
In this article, the botanical description of the ZINGIBER OFFICINALE L. plant, the introduction of the ZINGIBER OFFICINALE L. plant in the soil and climate conditions, and the distribution areas and seasonal development of the plant are based on the results of experiments.
Keywords: Zingiber officinale L; type; world; scientific